Financing structural change, venture capital, and unemployment: What is the role of investor protection? - Rainer Fehn (Bayerische Julius-Maximilians-Universität Würzburg, Lehrstuhl für Volkswirtschaftslehre, Wirtschaftsordnung und Sozialpolitik, 2000)
This paper analyzes the real effects of differences in structures on financial markets, especially concerning quasi-equilibrium unemployment. It argues that a vibrant venture capital market is an important prerequisite for financing structural change and thus for keeping unemployment low in the ongoing transition to the "new economy". It furthermore points out the crucial importance of extensive investor protection in this respect. A thriving venture capital market is therefore at odds with the corporatist politicoeconomic equilibrium in continental European countries involving extensive protection of insiders on labor as well as on financial markets.
Keywords: 330; Finanzmarkt; Unternehmensfinanzierung; Strukturwandel; Arbeitslosigkeit; Risikokapital; Anlegerschutz; Beschäftigungseffekt; OECD-Staaten